AB0683 Parameters of arterial stiffness in a population of SLE patients with long disease duration: Something new to be examined?. (23rd January 2014) - Carli, L.; Tani, C.; Bruno, R.; Ghiadoni, L.; Armenia, S.; Cartoni, G.; della Rossa, A.; Totti, D.; Taddei, S.; Bombardieri, S.; Mosca, M.
Abstract : Background: Patients with Systemic Lupus Erythematosus (SLE) are at increased risk to develop cardiovascular (CV) events. Arterial stiffness (AS) expresses structural changes in the arterial wall. The presence of AS can be detected with arterial tonometry, a non-invasive technique recording the waveform profile. In particular, carotid to femoral Pulse Wave Velocity (PWV) and the Augmentation Index (AI), the main parameters used for evaluating both arterial distensibility and stiffness, seems to predict cardiovascular events independent of traditional risk factors. Thus, evaluation of AS may serve as markers of subclinical arterial damage for the assessment of cardiovascular risk. Objectives: To study AS in a cohort of SLE patients with long disease duration prospectively followed at our unit and to investigate its relation with disease correlated variables. Methods: Arterial tonometry was performed in SLE patients with a disease duration >5 years, without overt cardiovascular involvement, consecutively seen at our Unit. Clinical history, including cumulative glucocorticoid dose (GC), traditional CV risk factors, laboratory parameters as well as a complete serological profile were recorded. Disease activity was evaluated with the ECLAM global score, while SLICC/ACR-DI was used to score disease damage. AS was assessed as carotid-to-femoral PWV by arterial tonometry (Sphygmocor). AI, an integrated parameter of wave reflection and arterial stiffness, was also assessed. Results: 24 patients (mean age was 42±11 years) with mean disease duration of 228±97 months (range 60-420 months) were enrolled. The mean ECLAM was 0.6 (min 0, max 2), the mean SLICC/ACR DI was 1 (min 0, max 6). At assessment systolic blood pressure (BP) was 128±17 mmHg, diastolic BP of 75±9 mmHg, and mean values of PWV and AI respectively of 7.8±1.7 m/s and23.9±8.8%. On univariate analysis PWV showed a significant correlation with age (r=0.68; p<0, 001), SLICC (r=0.71, p<0.001), mean BP (r=0.73: p<0.01). On multivariate analysis including these parameters, PWV was associated with age and mean BP while the association with the SLICC/ACR DI was not significant. In addition, univariate analysis showed a correlation between AI and total amount of GC (r 0, 48 p 0, 02), SLICC (r=0.58; p=0.006), serum creatinine (r=0.47; p=0.03) and age (r=0.58 p=0.003). While on multiple regression analysis (r 2 =0.64), only disease duration remained correlated with AI (p=0.04) Conclusions: Our data suggest that PWV, which reflects mainly AS, is influenced mostly by traditional cardiovascular risk factors, in particular by age. On the contrary AI, reflecting also the damage of microcirculation typical of SLE, appears to be correlated with disease duration. Thus, these vascular parameters could deserve as simple useful tools for integrated CV risk evaluation in SLE patients. Disclosure of Interest: None Declared